Assessment of Two Different Drinking Water Treatment Plants for the Removal of Free-living Amoebae, Egypt - AL-HERRAWY, Ahmad Z. (Iran J Parasitol, 2017)
BACKGROUND: The aim of this study was to compare between slow and rapid sand filters for the removal of free-living amoebae during drinking water treatment production. METHODS: Overall, 48 water samples were collected from two drinking water treatment plants having two different filtration systems (slow and rapid sand filters) and from inlet and outlet of each plant. Water samples were collected from Fayoum Drinking Water and Wastewater Holding Company, Egypt, during the year 2015. They were processed for detection of FLAs using non-nutrient agar (NNA). The isolates of FLAs were microscopically identified to the genus level based on the morphologic criteria and molecularly confirmed by the aid of PCR using genus-specific primers. RESULTS: The percentage of removal for FLAs through different treatment processes reached its highest rate in the station using slow sand filters (83%), while the removal by rapid sand filter system was 71.4%. Statistically, there was no significant difference (P=0.55) for the removal of FLAs between the two different drinking water treatment systems. Statistically, seasons had no significant effect on the prevalence of FLAs in the two different drinking water treatment plants. Morphological identification of the isolated FLAs showed the presence of 3 genera namely Acanthamoeba, Naegleria, and Vermamoeba (Hartmannella) confirmed by PCR. CONCLUSION: The appearance of FLAs especially pathogenic amoebae in completely treated drinking water may cause potential health threat although there is no statistical difference between the two examined drinking water filtration systems